The Effect of Telephone Follow-up on Lifestyle of Patients in Cardiac Care Units - Masoumeh Bagheri-Nesami; Attieh Nikkhah; Sharare Asgari; Soodabeh Aghapoor (Golestan University of Medical Sciences, 2020)
Background: Telephone follow-up is one of the effective ways to improve lifestyle of cardiac patients. Discharge planning is the development of an individualized discharge plan for the patient prior to leaving hospital, with the aim of improving patient outcomes. This study was done to investigate the effect of telephone follow-up after discharge on the lifestyle of cardiac patients. Methods: This randomized clinical trial was conducted on 154 cardiac patients in cardiac care units in Sari, Iran 2015-2016. Patients were recruited through convenient sampling, then they were allocated randomly in two experimental (n=77) and control (n=77) groups. Before registering, training was provided for both groups of patients. In next step, all the patients were followed up by telephone on the second, fourth and sixth days after the discharge. In addition, the experimental group was followed up by telephone weekly for a month and then monthly for five months. Data was gathered using questionnaire before intervention, as well as one and six months after intervention. Data was analyzed with repeated measures ANOVA, Chi-square and the independent t-test in SPSS-16. Results: No statistically significant differences were observed between the two groups in self-care, physical activity and exercise, diet and stress management score before intervention. However, significant differences were observed between the two groups in self-care (p<0.001), physical activity and exercise (p<0.001), diet (p<0.001), and stress management (p<0.001) score after intervention during 6 months. Conclusions: Telephone follow-up program is effective method promoting the cardiac self- patients lifestyle. The structured telephone follow-up was important for a holistic approach care in patients.